The House Edge and the Basic Strategy of Blackjack. - Cai, Xinyi (SHS Web of Conferences, 2022)
The fact about the blackjack is that the dealer gains advantages all the time in the normal casino since the rules can be changed by the casino. The way they change rules affects the probabilities of winning for both players and dealers. Therefore, it is important for the players to learn how could the house edge occur and the strategy to maximize their advantages individually. The theoretical analysis and simulations of the experiment by computer programs, for the sake of data, are the tools for solving the problems mentioned in this paper. The house edge is resulted by difference of the bet and the probability of winning the game, and the basic strategy created slightly advantages for the players in the case that house edge always exists.